The Factors Affecting Drug Abuse Among Addicted Women - Mohammad Mehdi Rahmati (Drug Control Headquarters, Research and Education Office, 2002)
The aim of this article is to describe and analyse some background factors that has some effect on the formation and continuity of addictive behavior among a sample of 1500 addicted persons on the 10 provinces of Iran. The article explores the processes under which the addictive behavior occures. Based on the findings of a survey research on a sample of 1500 drug abusers, it is concluded that factors such as addiction to cigarettes, alcohol, drug type, and methods and situations of approaching and access to drugs are effective in beginning of addiction. At last , the article pays special attention to addiction among women as the drug abusers.